2019
DOI: 10.3390/plants8050131
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dwarfing Gene Ddw1 on Height and Agronomic Traits in Spring Triticale in Greenhouse and Field Experiments in a Non-Black Earth Region of Russia

Abstract: Triticale is a relatively new crop which still possesses serious drawbacks that can be significantly improved by breeding. The dwarfing genes proved to be very useful in the development of new lodging resistant and productive cultivars of winter triticale. The aim of our research was to assess the effect of the Ddw1 dwarfing gene from rye on the agronomic valuable traits in spring triticale. The Ddw1 effect was studied in the greenhouse experiment in segregating the F2:3 population and in the field of F3:4 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
3
5
0
Order By: Relevance
“…Braun et al [ 33 ] recently identified a gibberellin 2-oxidase gene ( ScGA2ox12 ) as a candidate for Ddw1 in rye, which is located at 862 Mbp on chromosome 5R. As Ddw1 has been reported in spring and winter triticale [ 14 , 17 , 31 , 35 ] and as the QTL region coincides with the position of Ddw1 , we conclude that the 5R QTL corresponds to Ddw1 . Ddw1 is present in 20 of the 129 registered cultivars analyzed in this study and appears to have been increasingly used in recent years.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Braun et al [ 33 ] recently identified a gibberellin 2-oxidase gene ( ScGA2ox12 ) as a candidate for Ddw1 in rye, which is located at 862 Mbp on chromosome 5R. As Ddw1 has been reported in spring and winter triticale [ 14 , 17 , 31 , 35 ] and as the QTL region coincides with the position of Ddw1 , we conclude that the 5R QTL corresponds to Ddw1 . Ddw1 is present in 20 of the 129 registered cultivars analyzed in this study and appears to have been increasingly used in recent years.…”
Section: Discussionsupporting
confidence: 61%
“…In this study, we identified three medium- to large-effect QTL and fine-mapping indicated that two of them correspond to Rht12 and Ddw1 . While Ddw1 has been reported in triticale previously [ 14 , 17 , 31 , 35 ], Rht12 has not yet been reported in triticale.…”
Section: Discussionmentioning
confidence: 95%
“…The Gibberellin 2-Oxidase gene is considered a candidate for Ddw1, while its ortholog in wheat is considered to be the Rht12 gene [14,[26][27][28][29][30]. It is able to reduce the height of plants by 25-30%, but at the same time, it reduces the thousand grain weight and the weight of grains per ear [31][32][33][34][35][36][37]. Ddw1 is successfully used in triticale breeding in Poland, Romania, and other European countries [14,38,39].…”
Section: Introductionmentioning
confidence: 99%
“…However, beside reducing plant height, the dwarfing alleles Ddw1 may also reduce the grain weight per spike and the weight of 1000 grains. This negative effect of Ddw1 can be compensated for by the presence of Rht-B1b [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, markers targeting microsatellite locus REMS1218 are used for Ddw1 genotyping. REMS1218 (GenBank accession BE587316) contains (AG) 8 repeats and was originally discovered by the analysis of cDNA sequences in GenBank. It was mapped at the end of a long arm of chromosome 5R in rye population obtained by crossing cv.…”
Section: Introductionmentioning
confidence: 99%